A Rough Diamond: The Perils of the Kimberley Process - Rush, Savannah J.; Rozell, Elizabeth J (Archives of Business Research, 2017)
The purpose of this investigation is to determine the impact that the Kimberley Process has on diamond trade, diamond merchants, paramilitary groups, and governments throughout the world. The research question was whether the Kimberley Process is effective in combatting the sale of conflict diamonds in Africa. The investigation reached a conclusion that the Kimberley Process is an ineffective vehicle for the combat of the conflict diamond trade and that the existing process should be changed to provide greater enforcement and oversight. Suggestions are offered for improvements to the Kimberley Process Certification Scheme that would mitigate its shortcomings and ultimately regulate the mining and trade of conflict diamonds.